A stage IV lung squamous cell cancer patient with brain metastases, high PD-L1 & TMB, achieves pCR and long-term survival after immune-chemotherapy and radical surgery: a case report and literature review - Xu, Xiangyu; Ma, Zheng (Frontiers in Immunology, 2025)
Brain metastases occur in 40% of advanced NSCLC patients, with poorer prognosis in squamous subtypes. Immune checkpoint inhibitors (ICIs) combined with chemotherapy have revolutionized treatment, yet data on the systematic treatment of stage IV squamous non-small cell lung cancer with surgery remain limited. A 59-year-old male smoker presented with stage cT4N2M1b IVA squamous NSCLC and a solitary brain metastasis. Next-generation sequencing revealed programmed cell death ligand 1 (PD-L1) high expression (TPS=75%) and TMB-High (28.49 Mut/Mb) without driver mutations. After pembrolizumab plus platinum-based chemotherapy induced conversion therapy for 3 cycles, the brain lesion achieved pathological complete response (pCR) following resection, while the primary lung tumor showed major pathological response (MPR) post-surgery. Postoperative adjuvant chemoimmunotherapy and 2-year pembrolizumab maintenance were administered. Serial circulating tumor DNA (ctDNA) monitoring remained negative, with no recurrence observed over 50 months. This is the first reported case of long-term survival (PFS >50 months) in a PD-L1-high/TMB-High squamous NSCLC patient with brain metastasis treated with immunotherapy-based multimodal therapy. Our findings suggest that biomarker-guided strategies integrating systemic therapy, surgery, and MRD monitoring may enable curative potential in select advanced NSCLC patients. Further studies are warranted to validate this “sandwich” approach (drug-surgery-drug) and optimize treatment duration.